Portuguese state university performance according to students: an efficiency analysis - Mainardes, Emerson Wagner; Alves, Helena; Raposo, Mario (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2016)
The objective of this research project is to evaluate the performance of Portuguese state universities in accordance with the expectations and satisfactions of their students and through recourse to the DEA methodology and thus representing one of the very few studies analysing university performance based upon student perceptions. According to an output oriented Variable Returns to Scale model, handling the responses returned by 1,669 students, the results demonstrate that faculties generally attain a good relationship between student expectations and their levels of satisfaction. We furthermore conclude that university scale does not guarantee efficiency. Hence, irrespective of size, universities are able to ensure the satisfaction of their students. Finally, the results show that satisfying only certain expectations related to specific aspects does not prove sufficient to guaranteeing overall student satisfaction. The analysis also correspondingly finds that while some decision making units prove efficient in satisfying expectations on specific aspects, they fail to attain such efficiency in the overall perspective of students.